Expression of TaWRKY44, a wheat WRKY gene, in transgenic tobacco confers multiple abiotic stress tolerances - Wang, Xiatian; Zeng, Jian; Li, Ying; Rong, Xiaoli; Sun, Jiutong; Sun, Tao; Li, Miao; Wang, Lianzhe; Feng, Ying; Chai, Ruihong; Chen, Mingjie; Chang, Junli; et al. (Frontiers in Plant Science, 2015)
The WRKY transcription factors have been reported to be involved in various plant physiological and biochemical processes. In this study, we successfully assembled 10 unigenes from expressed sequence tags (ESTs) of wheat and designated them as TaWRKY44–TaWRKY53, respectively. Among these genes, a subgroup I gene, TaWRKY44, was found to be upregulated by treatments with PEG6000, NaCl, 4°C, abscisic acid (ABA), H2O2 and gibberellin (GA). The TaWRKY44-GFP fusion protein was localized to the nucleus of onion epidermal cells, and TaWRKY44 was able to bind to the core DNA sequences of TTGACC and TTAACC in yeast. The N-terminal of TaWRKY44 showed transcriptional activation activity. Expression of TaWRKY44 in tobacco plants conferred drought and salt tolerance and transgenic tobacco exhibited a higher survival rate, relative water content (RWC), soluble sugar, proline and superoxide dismutase (SOD) content, as well as higher activities of catalase (CAT) and peroxidase (POD), but less ion leakage (IL), lower contents of malondialdehyde (MDA), and H2O2. In addition, expression of TaWRKY44 also increased the seed germination rate in the transgenic lines under osmotic stress conditions while exhibiting a lower H2O2 content and higher SOD, CAT, and POD activities. Expression of TaWRKY44 upregulated the expression of some reactive oxygen species (ROS)-related genes and stress-responsive genes in tobacco under osmotic stresses. These data demonstrate that TaWRKY44 may act as a positive regulator in drought/salt/osmotic stress responses by either efficient ROS elimination through direct or indirect activation of the cellular antioxidant systems or activation of stress-associated gene expression.